PENERAPAN SISTEM INFORMASI AKUNTANSI PADA SISTEM PENJUALAN PRODUK REAL ESTAT PADA PT. X DI SURABAYA - Susan Febriany Sugiarto; Adhicipta Raharja Wirawan (CALYPTRA, 2018)
Abstract- This fieldwork research study aims to describe the experience when working especially in the real estate sector. In the discussion based on documentation of the process while working in this sector, especially in the staff of apprenticeship finance and accounting. The main focus of workmanship in a variety of tasks of commission realization. This research uses real experience in field work in a company. This study uses a sample of one of the real estate companies in Surabaya. This research was conducted in three months of field work commencing on 2 August 2017. After the fieldwork process has been completed, reporting started for two months of work. The research findings shows the flow of accounting information system in commission. This is related to cross-division at once, but the main focus remains on the financial and accounting division.